Pengabdian Masyarakat Pemeriksaan Kolesterol dengan Metode POCT dan Pemanfaatan Kulit Buah Naga Merah di Wilayah Mojokerto [Community Service Cholesterol Screening Using the POCT Method and Utilization of Red Dragon Fruit Peel in the Mojokerto Region] - Nidianti, Ersalina; Syahrah, Annisa; Pertiwi, Sarafia; Fauziyah, Luqiana; Lukiyono, Yauwan Tobing (UKInstitute, 2026)
Non-communicable diseases (NCDs), particularly hypercholesterolemia, are increasing health problems and major risk factors for cardiovascular disease. This community service activity aimed to measure cholesterol levels using the Point of Care Testing (POCT) method and to educate the community on utilizing red dragon fruit peel waste as a natural detection kit for borax and formalin. The program was conducted in Sumbersono Village, Dlanggu District, Mojokerto Regency, over one month (July 2025), targeting local residents and street food vendors around schools and markets. The methods included several stages: planning, cholesterol screening using a POCT device, education on interpreting the results, and the preparation and use of borax and formalin detection kits made from red dragon fruit peel extract. The results showed that approximately 40% of participants had cholesterol levels above normal limits, while 60% were within normal ranges. Testing of seven food samples using both commercial detection kits and natural indicators based on red dragon fruit peel extract yielded negative results for borax and formalin. In conclusion, this community service program successfully integrated health promotion and disease prevention efforts with the innovative use of agricultural waste (red dragon fruit peel). The application of red dragon fruit peel as a natural indicator proved effective, with all tested food samples showing negative results. Abstrak. Penyakit tidak menular (PTM), khususnya hiperkolesterolemia, merupakan masalah kesehatan yang terus meningkat dan menjadi faktor risiko utama penyakit kardiovaskular. Tujuan kegiatan pengabdian masyarakat ini untuk melakukan pemeriksaan kadar kolesterol menggunakan metode Point of Care Testing (POCT) serta mengedukasi pemanfaatan limbah kulit buah naga merah sebagai kit deteksi alami boraks dan formalin. Kegiatan dilaksanakan di Desa Sumbersono, Kecamatan Dlanggu, Kabupaten Mojokerto selama satu bulan (Juli 2025) dengan sasaran masyarakat desa dan pedagang jajanan di sekolah atau di pasar. Metode kegiatan meliputi perencanaan, pemeriksaan kadar kolesterol dengan alat POCT, edukasi hasil pemeriksaan, serta pemanfaatan kit uji boraks dan formalin berbasis ekstrak kulit buah naga merah. Hasil kegiatan menunjukkan bahwa sekitar 40% peserta memiliki kadar kolesterol melebihi batas normal, 60 % peserta kadar kolesterol normal. Pengujian kit deteksi komersial dan indikator alami berbasis ekstrak kulit buah naga merah pada 7 sampel diperoleh hasil negatif. Kesimpulan kegiatan pengabdian masyarakat ini berhasil mengintegrasikan aspek promotif dan preventif kesehatan dengan pemanfaatan limbah pertanian (kulit buah naga). Penggunaan kulit buah naga merah sebagai indikator alami terbukti efektif dengan semua sampel janan yang di uji menunjukkan hasil negatif.